Innovation Qris Adoption On MSMES In The Cashless Society Era: The Role Of Smoothness, Security & Convenience - Riwu, Yonas Ferdinand; Natonis, Sari Angriany; Aman, Dominikus T. Kopong; Manongga, Irience R Agatha (JURNAL MANAJEMEN DAN BISNIS, 2025)
Purpose – This study aims to analyze the influence of smoothness, security, and convenience on the decision to use QRIS by MSME actors in Kupang City. The focus of this research is in the context of the adoption of digital payment system technology in the MSME sector. Novelty – The novelty of this research lies in the focus of the MSME study area in Kupang City which has rarely received attention in the QRIS adoption study. This approach provides a more specific contextual understanding, as well as provides practical contributions for regulators and financial service providers. Method – Quantitative approximation was used in this study by collecting data through questionnaires to MSME actors using QRIS. The data analysis technique used was multiple linear regression to determine the influence of each variable on the decision to use QRIS Findings – The results of the study show that smoothness, security, and convenience have a positive and significant influence on the decision to use QRIS. Smoothness and security factors play an important role in forming trust and convenience in transactions, while ease increases the desire of MSMEs to adopt the technology. Limitations and Implications – This study is limited to the scope of MSMEs using QRIS in the Kupang City area, so generalizations to the wider population need to be cautious. The results of this study can be a reference for practitioners, financial service providers, and policymakers to improve QRIS implementation strategies through improving infrastructure, education, and digital literacy in the MSME sector.